Method for recovering copper oxide nanoflowers from acid waste etching liquid
By reacting and crystallizing with mixed alkali liquid in the acid waste etching liquid and calcining, the problem of recycling high-purity copper oxide nanoflowers from the acid waste etching liquid is successfully solved, and efficient and low-cost nanoflower recycling and application is achieved.
Patent Information
- Application Number
- CN202510670465.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-06-24
- Estimated Expiration
- 2045-05-23
AI Technical Summary
How to efficiently recover high-purity copper oxide nanoflowers from acidic waste etching liquid with complex compositions, and solve the problems of impure products and incomplete structures in traditional methods.
By mixing the acidic waste etching liquid with a specific composition mixed alkali liquid, controlling the pH value within the range of 8 to 13, performing heating reaction and crystallization to form copper oxide nanoflower crystals, and obtaining high-purity copper oxide nanoflower through calcination.
It has achieved efficient recycling of high-purity copper oxide nanoflowers from acidic waste etching liquid. The product has porous structure and rapid dissolution characteristics, and is suitable for electronic industry and other fields.
Smart Images

Figure CN120191956A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of waste etching solution treatment, and particularly to a method for recovering copper oxide nanoflowers from acidic waste etching solution. Background Art
[0002] The etching solution commonly used in the manufacturing process of printed circuit boards can be an acidic copper chloride etching solution with components of copper chloride and hydrochloric acid, or a basic copper chloride etching solution with components of copper chloride and ammonia water. Among them, after the etching process, the etching solution forms a waste etching solution containing high-concentration copper ions after dissolving copper. In traditional technologies, the methods for recovering copper from waste etching solution mainly include chemical precipitation method, solvent extraction method, and ion exchange method.
[0003] Copper oxide, as an important inorganic functional material, is widely used in the fields of electronics, energy, catalysis, chemical engineering, etc. Especially in the electronic industry, copper oxide is used as a raw material for copper electroplating, an electrode material for solar cells, and a catalyst for chemical reactions. Among them, nano-copper oxide shows broad application prospects in the fields of electronics, energy, and catalysis due to its unique physical and chemical properties. However, how to recover high-purity nano-copper oxide from waste etching solution with complex components is still a technical problem to be solved urgently. Summary of the Invention
[0004] Based on this, it is necessary to provide a method capable of recovering copper oxide nanoflowers from acidic waste etching solution.
[0005] The present application provides a method for recovering copper oxide nanoflowers from acidic waste etching solution, and the method includes:
[0006] Mixing an acidic waste etching solution containing copper ions and a mixed alkali solution to obtain a reaction solution with a pH of 8 - 13, and heating the reaction solution for reaction crystallization to form copper oxide nanoflower crystals. The mass concentration of the alkaline substance in the mixed alkali solution is 40% - 47%, and the alkaline substance includes an alkali hydroxide and an alkali carbonate with a mass ratio of (2.5 - 7.8):1; and,
[0007] Calcining the copper oxide nanoflower crystals to obtain copper oxide nanoflowers.
[0008] In some embodiments, the pH of the reaction solution obtained by mixing the acidic waste etching solution and the mixed alkali solution is 9.5 - 12.
[0009] In some embodiments, during the reaction crystallization process, the temperature of the reaction solution is 70°C - 95°C.
[0010] In some embodiments, the reaction crystallization time is 0.5 h - 2 h.
[0011] In some embodiments, during the reactive crystallization process, the reaction solution is stirred at a stirring speed of 10 rpm to 70 rpm.
[0012] In some embodiments, the hydroxide-based base includes at least one of sodium hydroxide and potassium hydroxide.
[0013] In some embodiments, the carbonate-based base includes at least one of sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.
[0014] In some embodiments, the calcination temperature is 200 °C to 600 °C, and the time is 0.5 h to 1.5 h.
[0015] In some embodiments, the acidic waste etching solution further contains impurity ions, and the impurity ions include at least one of iron ions, arsenic ions, and nickel ions. After removing the impurities from the acidic waste etching solution, the acidic waste etching solution containing copper ions is formed.
[0016] In some embodiments, the method for removing impurities includes: adding an oxidant to the acidic waste etching solution, and then adding metatitanic acid to adsorb and remove the impurity ions.
[0017] In some embodiments, the mass concentration of copper ions in the acidic waste etching solution is 50 g / L to 200 g / L.
[0018] In some embodiments, the copper oxide nanoflowers include a plurality of copper oxide porous nanosheets. The thickness of the copper oxide porous nanosheets is 10 nm to 100 nm, the length is 500 nm to 1000 nm, and the width is 300 nm to 1000 nm.
[0019] In some embodiments, the volume average particle size D50 of the copper oxide nanoflowers is 10 μm to 100 μm.
[0020] Compared with the traditional technology, the present application has at least the following beneficial effects:
[0021] The present application uses a mixed alkali solution with a specific composition to react with the acidic waste etching solution for reactive crystallization. During the reactive crystallization process, by controlling the pH, the content of the hydroxide-based base, and the carbonate-based base, copper ions can be first converted into intermediates of copper hydroxide and basic copper carbonate and then decomposed into copper oxide. Among them, the present application can promote the oriented nucleation and two-dimensional growth of the Cu(OH)2 precursor to form copper oxide nanosheets (with a thickness of about 10 nm), and CO3 in the basic copper carbonate 2-The decomposition and release of CO2 can play the roles of stirring, shearing, and microbubble templating, thereby guiding the formation of pores and driving the self-assembly of nanosheets to form cupric oxide nanoflower crystals with a three-dimensional nanoflower structure. The cupric oxide nanoflower crystals basically do not contain basic copper carbonate and copper hydroxide. After being calcined, they can form cupric oxide nanoflowers with high purity and a porous structure, which are applicable to fields such as copper electroplating, energy storage, solar cells, and chemical catalysts in the electronics industry. The recovery process of this application is simple and low-cost, achieving the recovery of high-purity cupric oxide nanoflowers from acidic waste etching solution, and the cupric oxide nanoflowers also have the characteristic of quickly dissolving in acidic solutions. Description of the Drawings
[0022] Figure 1 SEM comparison diagrams of the cupric oxide nanoflowers prepared in Example 1 of this application at different magnification ratios.
[0023] Figure 2 TEM diagram and EDX diagram of the cupric oxide nanoflowers prepared in Example 1 of this application.
[0024] Figure 3 X-ray diffraction diagram of the cupric oxide nanoflowers prepared in Example 1 of this application.
[0025] Figure 4 X-ray photoelectron spectroscopy (XPS) diagram of the cupric oxide nanoflowers prepared in Example 1 of this application.
[0026] Figure 5 SEM comparison diagrams of the cupric oxide nanoflowers prepared in Example 2 of this application at different magnification ratios.
[0027] Figure 6 SEM comparison diagrams of the cupric oxide nanoflowers prepared in Example 3 of this application at different magnification ratios.
[0028] Figure 7 SEM comparison diagrams of the cupric oxide nanoflowers prepared in Example 11 of this application at different magnification ratios.
[0029] Figure 8 SEM comparison diagrams of the cupric oxide products prepared in Comparative Example 1 of this application at different magnification ratios.
[0030] Figure 9 SEM comparison diagrams of the cupric oxide products prepared in Comparative Example 2 of this application at different magnification ratios.
[0031] Figure 10 X-ray diffraction diagram of the cupric oxide crystals after the reaction crystallization in step S2 of Comparative Example 3 of this application.
[0032] Figure 11SEM comparison diagrams of the copper oxide products prepared in Comparative Example 3 of this application at different magnification ratios.
[0033] Figure 12 SEM comparison diagrams of the copper oxide products prepared in Comparative Example 4 of this application at different magnification ratios.
[0034] Figure 13 SEM comparison diagrams of the copper oxide products prepared in Comparative Example 5 of this application at different magnification ratios. Detailed implementation manners
[0035] The following further describes this application in detail in combination with implementation manners and examples. These implementation manners and examples are only used to illustrate this application and not to limit the scope of this application. The purpose of providing these implementation manners and examples is to make the understanding of the disclosed content of this application more thorough and comprehensive. It should also be understood that this application can be implemented in many different forms and is not limited to the implementation manners and examples described herein. Those skilled in the art can make various changes or modifications without departing from the connotation of this application, and the equivalent forms obtained also fall within the protection scope of this application. In addition, in the following description, a large number of specific details are given to provide a more thorough understanding of this application. It should be understood that this application can be implemented without one or more of these details.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this application belongs. The terms used in the description of this application herein are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0037] In this application, "optionally", "optional", "option" mean optional, that is, it means any one selected from two parallel options of "having" or "not having". If "optional" appears multiple times in a technical solution, without special instructions and without contradictions or mutual restrictions, each "optional" is independent of each other.
[0038] In this application, in "the first aspect", "the second aspect", etc., the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0039] In this application, for the technical features described in an open-ended manner, it includes a closed technical solution composed of the listed features, and also includes an open technical solution containing the listed features.
[0040] In this application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the distribution of the selectable numerical values within the numerical interval is considered continuous, and it includes the two numerical endpoints of the numerical interval (i.e., the minimum value and the maximum value), as well as each numerical value between these two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, as well as each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all sub-ranges subsumed therein. The "numerical values" in the numerical interval can be any quantitative values, such as numbers, percentages, ratios, etc. The "numerical interval" is allowed to broadly include quantitative intervals such as percentage intervals, ratio intervals, and ratio value intervals.
[0041] All the documents mentioned in this application are cited as references in this application, just as if each document is cited separately as a reference. Unless it conflicts with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited for all their contents and all their purposes. When this application involves citing documents, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited together. When this application involves citing documents, the examples and preferred methods of the relevant technical features cited can also be incorporated as references into this application, but only to the extent that this application can be implemented. It should be understood that when the cited content conflicts with the description in this application, this application shall prevail or be amended adaptively according to the description in this application.
[0042] In the traditional technology, sodium hydroxide, potassium hydroxide, calcium carbonate, sodium carbonate, etc. are added to the acidic waste etching solution to precipitate basic copper carbonate or copper hydroxide. Among them, basic copper carbonate is an amorphous precipitate with a loose structure and a large specific surface area. It adsorbs a lot of impurities, is easily peptized, and has a large water content. Therefore, basic copper carbonate is not easy to filter and wash, and it needs to be calcined to obtain copper oxide. The copper hydroxide precipitate is unstable and easily dehydrates to form muddy copper oxide. The muddy copper oxide contains a relatively large amount of impurities, and the particles of the muddy copper oxide are small, the structure is loose, and it is relatively viscous, which is not conducive to the filtration and washing of the copper oxide product. In addition, most of the copper oxide nanoflowers are prepared by the method of crystal growth. It is necessary to directly grow copper oxide with a nanoflower structure on a specific growth substrate by a liquid phase method in cooperation with a surfactant, which not only has a high cost but also has a complex preparation process.
[0043] This application provides a method for recovering copper oxide nanoflowers from an acidic waste etching solution, and the method includes:
[0044] Mix the acidic waste etching solution containing copper ions with a mixed alkali solution to obtain a reaction solution with a pH of 8 - 13, and heat and react the reaction solution for crystallization to form copper oxide nanoflower crystals. The mass concentration of the alkaline substance in the mixed alkali solution is 40% - 47%, and the alkaline substance includes hydroxide bases and carbonate bases with a mass ratio of (2.5 - 7.8):1; and,
[0045] Calcine the copper oxide nanoflower crystals to obtain copper oxide nanoflowers.
[0046] Among them, the pH of the reaction solution obtained by mixing can be 8.0, 8.4, 8.8, 9.2, 9.6, 10.0, 10.4, 10.8, 11.2, 11.6, 12.0, 12.4, 12.8 or 13.0. The mass concentration of the alkaline substance in the mixed alkali solution can be 40.0%, 40.5%, 41.0%, 41.5%, 42.0%, 42.5%, 43.0%, 43.5%, 44.0%, 44.5%, 45.0%, 45.5%, 46.0%, 46.5% or 47.0%. The mass ratio of the hydroxide base to the carbonate base can be 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1, 5.0:1, 5.5:1, 6.0:1, 6.5:1, 7.0:1, 7.5:1 or 7.8:1.
[0047] In this application, a mixed alkali solution with a specific composition is used to react and crystallize with the acidic waste etching solution, which can form high-purity copper oxide nanoflower crystals with a nanoflower structure. And the copper oxide nanoflower crystals basically do not contain basic copper carbonate and copper hydroxide. After being calcined, it can form high-purity copper oxide nanoflowers with a porous structure, which are suitable for fields such as copper electroplating, energy storage, solar cells and chemical catalysts in the electronics industry. The recovery process of this application is simple and has low cost, realizing the recovery of high-purity copper oxide nanoflowers from the acidic waste etching solution, and the copper oxide nanoflowers also have the characteristic of quickly dissolving in acidic solutions.
[0048] By controlling the composition and content of the alkaline substance in the mixed alkali solution as above in this application, it effectively ensures that copper oxide nanoflower crystals can be formed after reaction crystallization, avoiding the formation of intermediate structures such as basic copper carbonate and copper hydroxide, which affect the purity of the copper oxide nanoflowers formed after calcination and the nanoflower structure. If the mass concentration of the alkaline substance in the mixed alkali solution is relatively low, it may lead to incomplete reaction and the inability to form a nanoflower structure. If the mass concentration of the alkaline substance in the mixed alkali solution is relatively high, it may lead to incomplete crystallization of the product and the inability to form a porous structure of the nanoflower, thereby affecting the dissolution rate of the copper oxide nanoflowers formed after calcination.
[0049] If the proportion of hydroxide alkali in the alkaline substance is relatively high, the copper oxide particles formed will contain more copper hydroxide, which usually appears as a blue flocculent precipitate and can be converted into copper oxide by high-temperature decomposition. However, due to the existence of particle sintering densification and Ostwald ripening effect, it is impossible to form a copper oxide product with a nanoflower structure after calcination. If the proportion of carbonate alkali in the alkaline substance is relatively high, the copper oxide particles formed will contain more basic copper carbonate. Similarly, basic copper carbonate can also be converted into copper oxide by high-temperature decomposition. However, due to the limitation of the precursor morphology, the basic copper carbonate precursor is an irregular dense particle, and the copper oxide tends to inherit its dense structure after decomposition; at the same time, the decomposition reaction of basic copper carbonate is violent, and the rapid escape of CO2 and H2O (especially at high temperature) will destroy the precursor skeleton, resulting in the collapse of the pore structure, rather than the formation of an ordered porous network, so that the copper oxide product with a nanoflower structure cannot be formed after calcination.
[0050] It should be noted that the copper ions in the acidic waste etching solution of the present application react with hydroxide to form a copper hydroxide intermediate, and react with carbonate to form basic copper carbonate. In the reaction environment of the present application, copper hydroxide is unstable and will decompose to form copper oxide; basic copper carbonate reacts with sodium hydroxide to form copper oxide and carbonate. Therefore, the copper oxide nanoflower crystals formed in the present application basically do not contain copper hydroxide and basic copper carbonate.
[0051] It is understandable that the present application does not make any specific requirements or special restrictions on the preparation method of the mixed alkali solution, and any mixed alkali solution with the above composition can be formed. For example, the mixed alkali solution can be prepared by mixing a solution containing a hydroxide alkali and a solution containing a carbonate alkali.
[0052] In some embodiments, the pH of the reaction solution obtained by mixing the acidic waste etching solution and the mixed alkali solution is 9.5 to 12. The present application further adjusts the pH of the mixed reaction solution to ensure that the copper ions in the acidic waste etching solution react completely and improve the recovery rate. It can also effectively reduce the copper salts remaining on the surface of the copper oxide nanoflower crystals, avoiding the residual copper salts from affecting the conversion and purity of the copper oxide nanoflowers during the calcination process.
[0053] In some embodiments, the temperature of the reaction solution during the reaction crystallization process is 70°C to 95°C, for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C or 95°C. It can be 80°C to 95°C.
[0054] The present application selects the reaction liquid temperature in the reaction crystallization process as above. From the perspective of kinetic control, since the temperature rise accelerates the Cu 2+The hydrolysis and precipitation reaction of CO3 shortens the nucleation induction period, and the conversion rate of Cu(OH)2 intermediate to CuO is moderate, which is conducive to the directional growth of nanosheets. 2- The CO2 bubbles generated by decomposition form microbubble templates to assist in the generation of pores, so that the nanoflower-like structure tends to grow during the crystallization process, further ensuring the formation of copper oxide nanoflowers after calcination. If the temperature is relatively low, due to insufficient reaction power and slow reaction speed, it may not be possible to form a porous and complete nanoflower structure, and there may be problems such as loose sheets; if the temperature is relatively high, due to the violent reaction, it may cause the crystal to grow explosively and the particles to agglomerate, and it is still impossible to form a nanoflower structure.
[0055] In some embodiments, the reaction crystallization time is 0.5 h to 2 h, for example, 0.5 h, 0.6 h, 0.8 h, 1.0 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2.0 h.
[0056] In some embodiments, the reaction solution is stirred during the reaction crystallization process at a speed of 10 rpm to 70 rpm. For example, the stirring speed may be 10 rpm, 15 rpm, 20 rpm, 25 rpm, 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm, 60 rpm, 65 rpm or 70 rpm. Optionally, the stirring speed may be 10 rpm to 60 rpm.
[0057] The stirring speed in the process of reaction crystallization is selected as above to promote Cu 2+ With OH - / CO3 2- The uniform mixing can avoid the explosive nucleation caused by excessive local concentration, and the moderate shear force can break up the initially agglomerated nanosheets, promote their directional arrangement, and ensure the crystal growth of copper oxide nanoflowers. When the stirring speed is relatively high, the self-assembly process of the nanosheets will be destroyed, resulting in the inability of the crystals to grow, and copper oxide nanoflowers cannot be formed after calcination.
[0058] In some embodiments, the hydroxide-based base includes at least one of sodium hydroxide and potassium hydroxide.
[0059] In some embodiments, the carbonate base includes at least one of sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.
[0060] In some embodiments, the calcination temperature is 200°C to 600°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, and can be 500°C to 590°C.
[0061] In some embodiments, the calcination time is 0.5 h to 1.5 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h.
[0062] The present application selects the calcination time and calcination temperature as above, which can further improve the crystallization of copper oxide and increase the thickness of the nanosheet layer (from 10nm to 15nm); it can also reduce lattice distortion and effectively maintain the integrity of the nanoflower structure, thereby ensuring the formation of a stable copper oxide nanoflower product. If the calcination temperature is relatively high, it may cause local sintering, blurring the edges of the copper oxide nanosheets, further reducing the specific surface area, and even causing the overall skeleton of the nanoflower to collapse, destroying the structure of the copper oxide nanoflower; if the calcination time is relatively long, the Oswald ripening effect may be aggravated during the calcination process, and the grains may be further coarsened to reduce the porosity. Although the mechanical strength can be improved, it will lead to a reduction in active sites. If the calcination temperature is relatively low or the time is relatively short, it may cause the residual internal stress of the crystal and the brittleness of the lamellae to be unable to be effectively improved, resulting in insufficient strengthening of the nanoflower structure, low product purity and dissolution rate, and other problems.
[0063] In some embodiments, the acid waste etching solution further contains impurity ions, and the impurity ions include at least one of iron ions, arsenic ions and nickel ions. The acid waste etching solution is subjected to impurity removal to form the acid waste etching solution containing copper ions. Optionally, the mass concentration of iron ions in the acid waste etching solution can be 5 mg / L to 80 mg / L, and the mass concentration of AsO4 3- The mass concentration of can be 1mg / L~30mg / L, and the mass concentration of nickel ions can be 1mg / L~20mg / L.
[0064] In some embodiments, the impurity removal method includes: adding an oxidant to the acidic waste etching solution, and then adding titanic acid to adsorb and remove impurity ions.
[0065] In some embodiments, when the color of the acidic waste etching solution turns to light green, the addition of the oxidant is stopped.
[0066] In some embodiments, the oxidizing agent comprises hydrogen peroxide.
[0067] In some embodiments, the amount of titanic acid added per unit volume of the acidic waste etching solution is 0.1 g / L to 2 g / L, for example, 0.1 g / L, 0.4 g / L, 0.8 g / L, 1.2 g / L, 1.4 g / L, 1.6 g / L or 2.0 g / L.
[0068] In some embodiments, during the impurity removal process, the pH of the acidic waste etching solution is 0.2-2, for example, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 or 2.0.
[0069] In some embodiments, the temperature of the acidic waste etching solution during the impurity removal process is 15°C to 50°C, for example, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C.
[0070] In some embodiments, the time for removing impurities is 10 min to 100 min, for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or 100 min.
[0071] In some embodiments, the acidic waste etching solution is stirred during the impurity removal process.
[0072] In some embodiments, the mass concentration of copper ions in the acidic waste etching solution is 50 g / L to 200 g / L, for example, 50 g / L, 60 g / L, 80 g / L, 120 g / L, 140 g / L, 160 g / L, 180 g / L or 200 g / L.
[0073] In some embodiments, the copper oxide nanoflowers include a plurality of copper oxide porous nanosheets, each of which has a thickness of 10 nm to 100 nm, a length of 500 nm to 1000 nm, and a width of 300 nm to 1000 nm.
[0074] In some embodiments, the volume average particle size D50 of the copper oxide nanoflowers is 10 μm to 100 μm.
[0075] Exemplarily, a method for recovering copper oxide nanoflowers from the above-mentioned acidic waste etching solution is provided, which specifically comprises the following steps:
[0076] S1. Add an oxidant to the acid waste etching solution containing copper ions and impurity ions until the acid waste etching solution turns light green, then add metatitanic acid to stir and remove impurities in the acid waste etching solution to remove impurities in the acid waste etching solution. The amount of metatitanic acid added per unit volume of the acid waste etching solution is 0.1 g / L~2 g / L, the pH of the acid waste etching solution during the impurity removal process is 0.2~2, the temperature is 15°C~50°C, and the impurity removal time is 10min~100min.
[0077] S2. Prepare a mixed alkali solution with a mass concentration of 40% to 47% of alkaline substances, wherein the alkaline substances include hydroxide alkalis and carbonate alkalis in a mass ratio of (2.5 to 7.8): 1. Mix the mixed alkali solution with the acidic waste etching solution after impurities removal in step S1 to obtain a reaction solution with a pH of 8 to 13, heat and stir the reaction solution, and react and crystallize at 70°C to 95°C and a stirring speed of 10rpm to 70rpm for 0.5h to 2h to form copper oxide nanoflower crystals. It is understood that after the reaction is completed, the reaction solution can be filtered and washed to separate the copper oxide nanoflower crystals.
[0078] S3. calcining the copper oxide nanoflower crystals formed in step S2 at 200° C. to 600° C. for 0.5 h to 1.5 h to obtain a high-purity, active copper oxide nanoflower product.
[0079] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0080] In the following examples, the copper ion concentration in the acid waste etching solution used was 105.2 g / L, the iron ion concentration was 23.4 mg / L, and the AsO4 3- The concentration of ions is 4.6 mg / L, the concentration of nickel ions is 3.6 mg / L, and the density of the acid waste etching solution is 1.103 g / L.
[0081] Example 1
[0082] S1. Add 30% hydrogen peroxide to 1L of acidic waste etching solution until the acidic waste etching solution turns light green, then add 1g of titanic acid to stir and remove impurities in the acidic waste etching solution at a pH of 1.5 and a temperature of 30°C for 30 minutes to remove iron, arsenic and nickel impurity ions in the acidic waste etching solution.
[0083] S2, a sodium hydroxide solution with a mass concentration of 50% and a sodium carbonate solution with a mass concentration of 29% are mixed in a volume ratio of 3:1 to obtain a mixed alkali solution, in which the mass concentration of the alkaline substance in the mixed alkali solution is 44.75%, and the mass ratio of sodium hydroxide to sodium carbonate in the alkaline substance is 6.17:1. The mixed alkali solution is mixed with the acidic waste etching solution after impurities are removed in step S1 to obtain a reaction solution with a pH of 11, the reaction solution is heated and stirred, and the reaction crystallization is carried out at 80°C and a stirring speed of 30rpm for 1h. After the reaction is completed, the reaction solution is filtered and washed to separate and form copper oxide nanoflower crystals.
[0084] S3. Calcinate the copper oxide nanoflower crystals formed in step S2 at 550 °C for 1 h to obtain a high-purity and active copper oxide nanoflower product.
[0085] Among them, Figure 1 are SEM images of the formed copper oxide nanoflowers in Example 1 at different ratios. Figure 1 As can be seen from a) and b) in, the product obtained in Example 1 appears as a black fine powder in appearance and has a multi-porous nanoflower structure microscopically. Further, from Figure 1 as can be seen from c) in, the copper oxide nanoflowers are composed of multiple nanosheets. Therefore, the average particle size of the copper oxide nanoflowers prepared in Example 1 is 20 µm and has a porous structure. Furthermore, Figure 2 are the transmission electron microscope (TEM) image and energy-dispersive X-ray spectroscopy (EDX) image of the formed copper oxide nanoflowers in Example 1. It can be seen from the TEM image that the copper oxide nanoflowers have a porous structure, and through the elemental analysis of the EDX image, it can be seen that copper elements and oxygen elements are evenly distributed in the copper oxide nanoflowers, indicating high purity and no impurities. Figure 3 is the X-ray diffraction pattern of the material in Example 1. It can be seen that the structure of the copper oxide nanoflowers is tenorite, belonging to the monoclinic system, with the chemical formula CuO, the space group C2 / c, and the unit cell parameters: a = 4.6853 Å, b = 3.4257 Å, c = 5.1303 Å, α = 90.0°, β = 99.549°, γ = 90.0°, and the unit cell volume 79.55 Å 3 , and the Z value is 4. Figure 4 is the X-ray photoelectron spectroscopy (XPS) image of the material in Example 1, and a detailed surface elemental composition and chemical state analysis of the copper oxide nanoflowers was carried out. It can be seen that there are two main peaks in the Cu 2p spectrum: the 2p3 / 2 peak is located at 933.6 eV and the 2p1 / 2 peak is located at 953.8 eV. Both of these peaks indicate that the oxidation state of Cu is +2, which is consistent with the chemical structure of CuO. In the O 1s spectrum, the peak at 529.6 eV belongs to lattice oxygen, and the peaks at 531.2 eV and 532.8 eV belong to adsorbed oxygen species, further revealing the surface chemical state of the copper oxide nanoflowers.
[0086] Example 2
[0087] S1. Add hydrogen peroxide with a mass concentration of 30% to 1 L of acidic waste etching solution until the acidic waste etching solution turns light green, and then add 2 g of metatitanic acid to stir and remove impurities from the acidic waste etching solution at pH 2 and a temperature of 40 °C for 20 min to remove iron, arsenic, and nickel impurity ions in the acidic waste etching solution.
[0088] S2. Mix a sodium hydroxide solution with a mass concentration of 50% and a sodium carbonate solution with a mass concentration of 29% in a volume ratio of 1.5:1 to obtain a mixed alkali solution. The mass concentration of the alkaline substances in the mixed alkali solution is 41.6%, and the mass ratio of sodium hydroxide to sodium carbonate in the alkaline substances is 2.6:1. Mix the above-mentioned mixed alkali solution with the acid waste etching solution after impurity removal in step S1 to obtain a reaction solution with a pH of 8. Heat and stir the reaction solution, and react and crystallize for 2 h at 95 °C and a stirring speed of 65 rpm. After the reaction is completed, filter and wash the reaction solution to separate and form copper oxide nanoflower crystals.
[0089] S3. Calcinate the copper oxide nanoflower crystals formed in step S2 at 500 °C for 1.5 h to obtain a high-purity and active copper oxide nanoflower product. The SEM image is as Figure 5 shown. The product appearance presents a black fine powder, and the microstructure is a multi-porous nanoflower structure.
[0090] Example 3
[0091] S1. Add hydrogen peroxide with a mass concentration of 30% to 1 L of acid waste etching solution until the acid waste etching solution turns light green. Then add 2 g of metatitanic acid and stir and remove impurities from the acid waste etching solution at a pH of 0.2 and a temperature of 15 °C for 40 min to remove iron, arsenic, and nickel impurity ions in the acid waste etching solution.
[0092] S2. Mix a sodium hydroxide solution with a mass concentration of 50% and a sodium carbonate solution with a mass concentration of 29% in a volume ratio of 4.5:1 to obtain a mixed alkali solution. The mass concentration of the alkaline substances in the mixed alkali solution is 46.2%, and the mass ratio of sodium hydroxide to sodium carbonate in the alkaline substances is 7.76:1. Mix the above-mentioned mixed alkali solution with the acid waste etching solution after impurity removal in step S1 to obtain a reaction solution with a pH of 13. Heat and stir the reaction solution, and react and crystallize for 0.5 h at 70 °C and a stirring speed of 15 rpm. After the reaction is completed, filter and wash the reaction solution to separate and form copper oxide nanoflower crystals.
[0093] S3. Calcinate the copper oxide nanoflower crystals formed in step S2 at 600 °C for 0.5 h to form a high-purity and active copper oxide nanoflower product. The SEM image is as Figure 6 shown. The product appearance presents a black fine powder, and the microstructure is a multi-porous nanoflower structure.
[0094] Example 4
[0095] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S2, the mixed alkali solution was mixed with the impurity-removed acidic waste etching solution to obtain a reaction solution with a pH of 9. The formed product had a black fine powder appearance and a multi-porous nanoflower structure microscopically.
[0096] Example 5
[0097] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S2, the temperature of the reaction solution during the reaction crystallization process was 60 °C. The formed product had a blue-brown fine powder appearance and a multi-porous nanoflower structure microscopically.
[0098] Example 6
[0099] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S2, the temperature of the reaction solution during the reaction crystallization process was 75 °C. The formed product had a black fine powder appearance and a multi-porous nanoflower structure microscopically.
[0100] Example 7
[0101] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S2, the temperature of the reaction solution during the reaction crystallization process was 100 °C. The formed product had a brownish-black fine powder appearance, but there were agglomerated particles, and a multi-porous nanoflower structure microscopically.
[0102] Example 8
[0103] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S2, the stirring speed of the reaction solution was 5 rpm. The formed product had a brownish-black fine powder appearance, the particles were relatively large, and a multi-porous nanoflower structure microscopically.
[0104] Example 9
[0105] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S2, the stirring speed of the reaction solution was 80 rpm. The formed product had a brownish-black fine powder appearance and a multi-porous nanoflower structure microscopically.
[0106] Example 10
[0107] The copper oxide nanoflowers were recovered from the acidic waste etching solution according to the method of Example 1, except that in step S3, the calcination temperature was 150 °C. The formed product had a brownish-black fine powder appearance and a multi-porous nanoflower structure microscopically.
[0108] Example 11
[0109] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the calcination temperature in step S3 is 700 °C. The SEM image of the formed cupric oxide nanoflowers is as Figure 7 shown. The appearance of the formed product presents as fine black powder, and there are some agglomerates. Microscopically, it has a nanoporous nanoflower structure.
[0110] Example 12
[0111] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the calcination time in step S3 is 20 min. The appearance of the formed product presents as fine dark brown powder. Microscopically, it has a nanoporous nanoflower structure.
[0112] Example 13
[0113] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the calcination time in step S3 is 2 h. The appearance of the formed product presents as fine black powder, but there are some agglomerates. Microscopically, it has a nanoporous nanoflower structure.
[0114] Comparative Example 1
[0115] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the mass concentration of the mixed alkali solution is 35%. The SEM image of the formed cupric oxide is as Figure 8 shown. The appearance of the product presents as fine gray-green powder, there are obvious agglomerated particles, and the microscopic structure is dense and does not have a nanoflower structure.
[0116] Comparative Example 2
[0117] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the mass concentration of the mixed alkali solution is 55%. The SEM image of the formed cupric oxide is as Figure 9 shown. The appearance of the product presents as fine dark gray powder, and microscopically it does not have a nanoflower structure.
[0118] Comparative Example 3
[0119] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the mass ratio of sodium hydroxide to sodium carbonate in the mixed alkali solution is 2:1. The SEM image of the formed cupric oxide is as Figure 11 shown. The appearance of the product presents as fine brownish powder, and microscopically it does not have a nanoporous nanoflower structure.
[0120] Comparative Example 4
[0121] Recover cupric oxide nanoflowers from acidic waste etching solution according to the method of Example 1, except that the mass ratio of sodium hydroxide to sodium carbonate in the mixed alkali solution is 9:1. The SEM image of the formed cupric oxide is asFigure 12 As shown, the product appearance presents a brownish - tan fine powder, and microscopically it does not have a nanoflower structure.
[0122] Comparative Example 5
[0123] Copper oxide nanoflowers were recovered from acidic waste etching solution according to the method of Example 1, except that step S3 was not carried out, and the copper oxide nanoflower crystals were directly used as the recovered product. The SEM image of the copper oxide nanoflower crystals is as Figure 13 shown. The product appearance presents a brownish - tan fine powder. Although it has a nanoflower structure microscopically, its porosity is poor.
[0124] The recovered products prepared in the above - mentioned examples and comparative examples were tested. The test methods include:
[0125] Standard characterization of product morphology: The recovered product was observed using SEM.
[0126] Purity test: The proportion of copper oxide in the recovered product.
[0127] Test for copper content in the overflow mother liquor: The copper content in the overflow mother liquor discharged in step S2 during the preparation process was detected.
[0128] Dissolution rate test: The recovered product was dissolved in an acidic solution with a mass ratio of concentrated sulfuric acid (mass concentration of 98%) to water of 1:9, and the time for complete dissolution was recorded.
[0129] The test results are shown in Table 1.
[0130] Table 1
[0131]
[0132] As can be seen from the above table:
[0133] (1) Comparing Example 1 with Example 4, it can be seen that by further controlling the pH of the reaction solution in this application, the crystallization of copper oxide can be made more uniform, the crystal configuration is more complete, and thus it has a better dissolution effect.
[0134] (2) Comparing Example 1 with Examples 5 - 7, it can be seen that by controlling the temperature of the reaction solution during the reaction crystallization process in this application, if the temperature is relatively low, it may cause insufficient reaction driving force and slow reaction speed, resulting in loose nanoflower - structure lamellae and poor porosity effect, affecting the dissolution effect of the product. If the temperature is relatively high, it may cause violent reactions, leading to explosive crystal growth and particle agglomeration problems, affecting the dissolution effect of the product. Therefore, an appropriate temperature is beneficial to the directional growth of nanosheets, effectively ensuring the formation of copper oxide products with a nanoporous nanoflower structure.
[0135] (3) Comparing Example 1 with Examples 8-9, it can be seen that by controlling the stirring speed during the reaction crystallization process in the present application, it is possible to avoid excessive local concentration leading to burst nucleation and the inability of crystals to grow, thereby promoting the oriented arrangement of copper oxide, ensuring the crystalline growth of copper oxide nanoflowers, and enhancing the dissolution effect. If the stirring speed is relatively low, it may cause a relatively high copper content in the overflow mother liquor, resulting in problems such as incomplete reaction of copper ions, insufficient liquid shear force, and crystal aggregation.
[0136] (4) Comparing Example 1 with Examples 10-13, it can be seen that by controlling the calcination temperature and time in the present application, it is possible to avoid local sintering and caking as well as damage to the microscopic morphology, thereby significantly improving the crystallinity of CuO and enhancing the dissolution effect. Combining Figure 7 it can be seen that in Example 11, the edges of the nanosheets are blurred, the nanoflower structure is damaged, resulting in a further reduction in the specific surface area, thereby affecting the dissolution effect.
[0137] (5) Comparing Example 1 with Comparative Examples 1-5, it can be seen that in Comparative Example 1, the mass concentration of the mixed alkali solution is relatively low, and the copper content in the overflow mother liquor discharged from the reaction crystallization is high, resulting in a relatively low primary recovery rate of copper resources and increasing the difficulty and cost of subsequent wastewater treatment. At the same time, Comparative Example 1 also has problems such as insufficient energy for the conversion of copper oxide and the easy generation of by-products (basic copper chloride). Combining Figure 8 with the SEM images, it can be seen that in Comparative Example 1, the particles are severely agglomerated, and there is almost no nanoflower structure, with a small specific surface area of the material and a slow dissolution rate. In Comparative Example 2, the mass concentration of the mixed alkali solution is relatively high, and due to incomplete crystallization, a nanoflower structure cannot be formed (as shown in the Figure 9 SEM images), and there are also problems such as waste of alkali solution and increased washing water consumption. In Comparative Example 3, the proportion of sodium hydroxide is relatively low. As shown in the Figure 10 X-ray diffraction pattern, the content of basic copper carbonate is relatively high during the formation of the intermediate, and the gas generated during its decomposition is likely to damage the nanostructure and affect the crystalline growth of the nanosheets, resulting in the collapse of the nanoflower structure. Therefore, a nanoflower structure cannot be formed (as shown in the Figure 11 SEM images). In Comparative Example 4, the proportion of sodium hydroxide is relatively high, and amorphous growth of copper oxide occurs, with a finer crystal form. As shown in the Figure 12 SEM images, a nanoflower structure still cannot be formed. In Comparative Example 5, no calcination treatment is carried out. As shown in the Figure 13 SEM images, the formed copper oxide nanoflower crystals have distorted copper oxide crystal forms and reduced crystallinity. Although they have a nanoflower structure, the pore effect is poor. According to the BET test, the specific surface area of copper oxide in Comparative Example 5 is 2.41 m 2 / g, and the pore volume is 0.012 cm 3 / g, while the specific surface area of Example 1 after calcination treatment reaches 9.31 m 2 / g, the pore volume reaches 0.025 cm 3 / g.
[0138] In summary, the present application uses a mixed alkali solution with a specific composition to react and crystallize with an acidic waste etching solution, which can form cupric oxide nanoflower crystals with a high crystallinity nanoflower structure and fast dissolution characteristics, and the cupric oxide nanoflower crystals basically do not contain basic copper carbonate and copper hydroxide. After being calcined, it can form high-purity cupric oxide nanoflowers with a porous structure, which are suitable for fields such as copper electroplating, energy storage, solar cells, and chemical catalysts in the electronics industry. The recovery process of the present application is simple and low in cost, realizing the recovery of high-purity cupric oxide nanoflowers from acidic waste etching solutions.
[0139] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope described in this specification.
[0140] The above-described embodiments only represent several implementation manners of the present application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the application. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several modifications and improvements can still be made, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the appended claims.
Claims
1. A method for recovering copper oxide nanoflowers from acidic waste etching solution, characterized in that, The method includes: Mixing an acidic waste etching solution containing copper ions and a mixed alkali solution to obtain a reaction solution with a pH of 8 - 13, and heating the reaction solution for reaction crystallization to form copper oxide nanoflower crystals. The mass concentration of the alkaline substance in the mixed alkali solution is 40% - 47%, and the alkaline substance includes a hydroxide base and a carbonate base with a mass ratio of (2.5 - 7.8):1; and, Calcining the copper oxide nanoflower crystals to obtain copper oxide nanoflowers.
2. The method for recovering cupric oxide nanoflowers from the acidic waste etching solution according to claim 1, characterized in that, The pH of the reaction solution obtained by mixing the acidic waste etching solution and the mixed alkali solution is 9.5 - 12.
3. The method for recovering cupric oxide nanoflowers from the acidic waste etching solution according to claim 1, characterized in that, The method also satisfies at least one of the following conditions: (1) During the reaction crystallization process, the temperature of the reaction solution is 70°C - 95°C; (2) The reaction crystallization time is 0.5 h - 2 h.
4. The method for recovering cupric oxide nanoflowers from acidic waste etching solution according to claim 1, characterized in that, During the reaction crystallization process, the reaction solution is stirred at a stirring speed of 10 rpm - 70 rpm.
5. The method for recovering copper oxide nanoflowers from the acidic waste etching solution according to claim 1, characterized in that, The method also satisfies at least one of the following conditions: (1) The hydroxide base includes at least one of sodium hydroxide and potassium hydroxide; (2) The carbonate base includes at least one of sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.
6. The method for recovering cupric oxide nanoflowers from the acidic waste etching solution according to claim 1, characterized in that, The calcination temperature is 200°C - 600°C, and the time is 0.5 h - 1.5 h.
7. The method for recovering copper oxide nanoflowers from the acidic waste etching solution according to any one of claims 1-6, characterized in that, The acidic waste etching solution also contains impurity ions, and the impurity ions include at least one of iron ions, arsenic ions, and nickel ions. After removing the impurities from the acidic waste etching solution, the acidic waste etching solution containing copper ions is formed.
8. The method for recovering cupric oxide nanoflowers from acidic waste etching solution according to claim 7, characterized in that, The method for removing impurities includes: adding an oxidant to the acidic waste etching solution, and then adding metatitanic acid to adsorb and remove the impurity ions.
9. The method for recovering copper oxide nanoflowers from the acidic waste etching solution according to any one of claims 1-6, characterized in that, The mass concentration of copper ions in the acidic waste etching solution is 50 g / L - 200 g / L.
10. The method for recovering cupric oxide nanoflowers from the acidic waste etching solution according to any one of claims 1-6, characterized in that, The copper oxide nanoflower includes a plurality of copper oxide porous nanosheets. The thickness of the copper oxide porous nanosheets is 10 nm - 100 nm, the length is 500 nm - 1000 nm, and the width is 300 nm - 1000 nm; The volume average particle size D50 of the copper oxide nanoflower is 10 μm - 100 μm.
Citation Information
Patent Citations
Method for preparing high-purity cupric oxide powder from acid cupriferous waste liquid
CN101549882A
Production method of high-purity electroplating grade copper oxide
CN103739000A
Production of copper oxide
JP1996002915A
Method for preparing high purity copper oxide containing a trace amount of chlorine from waste etchant
KR100840553B1